Meningkatkan Prestasi Belajar IPA Materi Saling Ketergantungan Antara Komponen Biotik dan Abiotik Dengan Menggunakan Metode Pengamatan Lapangan - sakirin sakirin (Universitas Hamzanwadi, 2019)
Classroom action research (PTK) aims to improve the learning achievement of science material interdependence between biotic and abiotic components through the field observation method. The method used is Classroom Action Research which is carried out using four stages, namely; (1) Planning, (2) Implementation, (3) observation, and (4) Reflection. The four stages are carried out in 2 cycles, namely cycle I and cycle II, and each cycle consists of 2 meetings. Based on the results of the pre-cycle tests, it was found that the average value of students was 54.6, with only 8 people or 28.6% who had achieved KKM = 65 and 20 people or 71.4% had not yet reached KKM. Then, the results of the test post in the first cycle obtained an average value of 70. In this cycle the number of students who completed increased to 18 people or 64.3% and those who did not complete as many as 10 people or 35.7% Furthermore, in the second cycle the value the average student has reached 76.4, with 25 people or 89.3% who have completed and 3 people or 10.7% who have not finished. These data indicate that the learning achievement of science material interdependence between biotic and abiotic components has increased cycle after cycle